Paeoniflorin protects spiral ganglion neurons from cisplatin‐induced ototoxicity: Possible relation to PINK1/BAD pathway. Issue 8 (17th June 2019) - Yu, Xiaoyu; Man, Rongjun; Li, Yanan; Yang, Qianqian; Li, Hongrui; Yang, Huiming; Bai, Xiaohui; Yin, Haiyan; Li, Jianfeng; Wang, Haibo
Abstract: The objective of this study was to elucidate whether paeoniflorin (PF) exerted an effect on cisplatin‐induced spiral ganglion neuron (SGN) damage, with special attention given to the role of PINK1/BAD pathway in this process. Middle cochlear turn culture and C57BL/6 mice were utilized to identify the character of PF in vitro and in vivo. We found that cisplatin treatment led to SGN damage, in which reactive oxygen species (ROS) generation increased, PINK1 expression decreased, BAD accumulation on mitochondria raised and mitochondrial apoptotic pathway activated. Conversely, we demonstrated that PF pre‐treatment obviously mitigated cisplatin‐induced SGN damage. Mechanistic studies showed that PF could reduce ROS levels, increase PINK1 expression, decrease the BAD accumulation on mitochondria and, thus, alleviate the activated mitochondrial apoptosis in SGNs caused by cisplatin. Overall, the findings from this work reveal the important role of PF and provide another strategy against cisplatin‐induced ototoxicity.